Réflexions sur l’étonnement et l’enseignement de la philosophie au pré-universitaire - Chiara Cavalli (Éducation et Socialisation)
The objective of this research is to understand the astonishment experienced by students during a pre-university philosophy courses. Several arguments from the philosophical and pedagogical tradition, and also from recent studies in educational philosophy and philosophy for children, show that astonishment is an important experience in the process of learning philosophy. This experience could enable students to grasp the meaning of philosophical questions and the need for research that it implies. However, despite the importance of these arguments, descriptive elements of the experience of astonishment during philosophy courses by the students are still needed. For this reason, and in order to illuminate precisely the role of this experience as part of learning philosophy, the testimonies of ten experiences of astonishment during the pre-university philosophy courses were obtain according to a methodological device inspired by phenomenological approaches in education.